2007
DOI: 10.1136/ard.2007.082560
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the content and conduct of European League Against Rheumatism (EULAR) musculoskeletal ultrasound courses

Abstract: Objective:To develop education guidelines for the conduct of future European League Against Rheumatism (EULAR) musculoskeletal ultrasound (MSUS) courses.Methods:We undertook a consensus-based, iterative process using two consecutive questionnaires sent to 29 senior ultrasonographer rheumatologists who comprised the faculty of the 14th EULAR ultrasound course (June 2007). The first questionnaire encompassed the following issues: type of MSUS educational model; course timing; course curriculum; course duration; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 23 publications
0
48
0
8
Order By: Relevance
“…These have contributed to the development of essential issues, MSUS training method and competency assessment in rheumatology [24][25][26][27][28][29][30][31]. More recently, training in ultrasound-guided injections for rheumatologists among countries has been tested and results demonstrated that the percentage of rheumatologists receiving training in the field is <10% in over 70% of countries that participated in the survey [32].…”
Section: Education and Training In Msusmentioning
confidence: 99%
See 2 more Smart Citations
“…These have contributed to the development of essential issues, MSUS training method and competency assessment in rheumatology [24][25][26][27][28][29][30][31]. More recently, training in ultrasound-guided injections for rheumatologists among countries has been tested and results demonstrated that the percentage of rheumatologists receiving training in the field is <10% in over 70% of countries that participated in the survey [32].…”
Section: Education and Training In Msusmentioning
confidence: 99%
“…In 2007, the rheumatologists (from 11 European countries) who make up the faculty giving these courses developed educational guidelines for the content and conduct of EULAR ultrasound courses; these are recommended for national and local MSUS training programmes. They might also be useful for standardising rheumatology MSUS training worldwide [31].…”
Section: Forms Of Msus Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…This has reinforced the need for adequate training by rheumatologists to learn the techniques in order to improve their clinical practice [3]. As such, models to support the learning needs of rheumatologists in the use of US have been devised in Europe and the USA [3,84,85]. Additionally, the uptake of US by other nonmedical clinicians, such as rheumatology specialist nurses, physiotherapists and podiatrists, is gaining recognition [2].…”
Section: Us Use In Assessing Efficacy Of Interventions For Ra Foot DImentioning
confidence: 99%
“…In 2012 a working group was created under the umbrella of The European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB), with the mission of developing a competency assessment system for rheumatologists in MSUS. This competency assessment was based on an already existing EFSUMB competency assessment for musculoskeletal ultrasound in general [1,2], on the recommendations for the curriculum of the European League Against Rheumatism (EULAR) MSUS courses [3] and on a consensus of the working group.…”
Section: Introductionmentioning
confidence: 99%